Investigating the associations between dietary nutrient intake and risk of Hashimoto’s thyroiditis: a cross-sectional study from NHANES and a case-control study - Wang, Yicheng; Zhang, Lina; Wang, Xinqi; Yuan, Xiangyi; Huang, Qingling; Wang, Hao; Song, Qingyuan; Li, Duo; Kan, Hui; Li, Jiaomei (Frontiers in Nutrition, 2025)
BackgroundHashimoto’s thyroiditis (HT) is a prevalent autoimmune disorder and a leading cause of hypothyroidism, with an increasing incidence worldwide. Emerging evidence suggests that dietary nutrients intake may influence the development and progression of HT.MethodsData from the 2009–2012 National Health and Nutrition Examination Survey (NHANES) were analyzed to examine associations between dietary nutrient intake and HT risk among 2,732 participants. Nutrient intakes were categorized into quartiles, with the lowest quartile (Q1) serving as the reference. Weighted multivariable logistic regression models were applied to assess associations, and restricted cubic splines models were used to evaluate potential nonlinear relationships. To validate the NHANES findings and reduce potential biases arising from dietary assessment inaccuracies and racial differences, a case-control study was conducted to investigate the association between erythrocyte phospholipid fatty acids and HT risk using logistic regression models.ResultsNo significant correlations were found between HT risk and the intake of carbohydrates, sugars, fiber, vitamin C, vitamin D, vitamin E, magnesium, or zinc (p > 0.05). In contrast, higher total polyunsaturated fatty acids (PUFAs) and α-linolenic acid (C18:3 n-3) intake were significantly associated with lower HT risk (p < 0.05), although no nonlinear relationships were observed. Subgroup analysis revealed that α-linolenic acid intake was significantly lower in females than in males, potentially contributing to their greater susceptibility to HT. In the validation study, higher erythrocyte membrane levels of total n-3 PUFAs (OR = 0.616, 95% CI: 0.443–0.992, p = 0.041), C18:3 n-3 (OR = 0.627, 95% CI: 0.558–0.874, p = 0.037) and eicosapentaenoic acid (EPA, C20:5 n-3; OR = 0.736, 95% CI: 0.581–0.975, p = 0.042) were significantly associated with a low prevalence of HT.ConclusionThe findings suggest that insufficient n-3 PUFAs intake may be a potential risk factor of Hashimoto’s thyroiditis. Clinical trials are warranted to evaluate whether n-3 PUFA supplementation could help prevent or mitigate thyroid autoimmunity.